Red Blood Cell Distribution Width (RDW) as a prognostic marker for COVID-19: A literature review (Research, Society and Development, 2021)
The Red Cell Distribution Width (RDW) is a component of blood count which gives the variation of erythrocytes, used in laboratory hematology. The analysis of this parameter is in evidence, as the increased levels of RDW seem to be a mortality predictor. The infections of the respiratory tract are in these conditions and the increase of RDW has already been related to severe acute respiratory syndrome (SARS). In December of 2019, the first cases of severe acute pneumonia caused by the SARS-CoV-2 virus emerged in China. The Corona Virus Disease-19 (COVID-19) has as most common clinical manifestations changes in the respiratory tract that range from mild to severe symptoms, requiring respiratory support in severe cases. Current evidence point to the increase of RDW value which is related to severity of the disease and mortality rates due to COVID-19. The large number of severe cases of COVID-19 shows the urgent of the identification of cheap diagnostic parameters and easy detection, which could be used for determining the prognosis of these patients. The RDW has been shown to be a potential biomarker due to the easy obtaining, low cost, and therefore, it can be an important guide to early and effective interventions.